Intestinal parasitic infections among school children in Kuantan area - Mohammad, Mardhiah; Mat Yusof, Afzan; Hisamuddin, Nur Hazirah; Hashim, Najat; Soffian, Sharmeen Nellisa; Md Isa, Muhammad Lokman (2016)
The intestinal parasitic infections are usually caused by helminths and protozoa that can lead to the public health problem such as acute and chronic diarrhea, dehydration and abdominal pain. Common factors that cause intestinal parasitic infection among school children are poor hygiene habits, overcrowding, drinking unsafe water and poor immnunity. Therefore, the study aimed to identify the presence of the protozoa and helminths among school children aged 10 years old from four different schools in Kuantan, Pahang. The informed consent form is given to parents before conducting this research. Only 62 school children were willing to participate in this study. The collected stool specimens were examined microscopically by direct smear for detecting the presence of helminths. Trichrome staining and modified Ziehl-Neelsen staining were performed to identify the presence of cysts and oocysts.